1984
DOI: 10.1007/bf00159350
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of uranium to Daphnia magna

Abstract: The toxicity of U to Daphnia magna was determined in acute and chronic tests. The 48-hr LCso of U (VI) in Columbia River water was 6 mg L -~. Acute toxicity diminished by a factor of 7.5 as mean water hardness and alkalinity values increased from 70 mg L -~ and 57 mg L l to 195 mg L -~ and 130 mg L ~, respectively. This effect was most likely the result of complexation of uranyl ion with carbonate ions. D. magna reproduction was suppressed in Columbia River water at U concentrations between 0.5 and 3.5 mg L ~.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 7 publications
2
31
1
Order By: Relevance
“…The next series of papers (Trapp, 1986;Hyne et al, 1992a,b;Bywater et al, 1991;Poston et al, 1984;Barata et al, 1999) all reported effect concentrations that graded from 0.15 to 0.9 mg U L ÿ1 , with no distinct groupings of effect concentrations. This is a typical and expected outcome for a summary of ecotoxicology results, because it reflects the fact that there is a continuum of effect concentrations over a series of the many possible organisms and endpoints.…”
Section: Relative To Water Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next series of papers (Trapp, 1986;Hyne et al, 1992a,b;Bywater et al, 1991;Poston et al, 1984;Barata et al, 1999) all reported effect concentrations that graded from 0.15 to 0.9 mg U L ÿ1 , with no distinct groupings of effect concentrations. This is a typical and expected outcome for a summary of ecotoxicology results, because it reflects the fact that there is a continuum of effect concentrations over a series of the many possible organisms and endpoints.…”
Section: Relative To Water Concentrationsmentioning
confidence: 99%
“…Poston et al (1984) did a screening level test and at 96 h only saw mortality at 100 mg L ÿ1 , it was 16% mortality so this was recorded as an LC 16 . Water hardness was 70 mg L ÿ1 .…”
Section: Very Soft Watermentioning
confidence: 99%
“…Several other studies have determined the effects of increasing water hardness on the toxicity of U to freshwater organisms (fish [105]; water flea [106,107]). However, because these studies confounded the effects of increasing water hardness with increasing alkalinity and pH, the true effects of water hardness (i.e., Ca and/or Mg concentration) on U toxicity could not be discerned.…”
Section: Effect Of Water Hardnessmentioning
confidence: 99%
“…j No AWQC available; value is lowest concentration reported as chemotoxic to aquatic biota (Poston et al 1984).…”
Section: Benchmark Valuesmentioning
confidence: 99%